Sustainable ICT education ecosystem - Chin, Kum; Chang, Elizabeth (IEEE Industrial Electronics Society, 2009)
ICT education at Tertiary level in Australia is currently faced with the crisis of low student enrolments despite strong demand from the industry. This has resulted in financial sustainability issues for many university schools/departments offering ICT education. We have seen a large number of Schools or Departments known as e-Commerce, Software Engineering, Information Systems, and Computer Science in Australian Universities have shut down or merged with other Engineering or Business faculties in the last 6 years. This paper examines some findings of this crisis and proposes a framework of a sustainable ICT education ecosystem at tertiary level that may be the model to address the current crisis. The framework is inspired by the foundation of the sustainable ecological ecosystems in nature and we provide conceptual mapping of the ICT education ecosystems to the sustainable ecological ecosystem.